Dual function of Rpn5 in two PCI complexes, the 26S proteasome and COP9 signalosome - Yu, Zanlin (The American Society for Cell Biology, 2011)
Subunit composition and architectural structure of the 26S proteasome lid is strictly conserved between all eukaryotes. This eight-subunit complex bears high similarity to the eukaryotic translation initiation factor 3 and to the COP9 signalosome (CSN), which together define the proteasome CSN/COP9/initiation factor (PCI) troika. In some unicellular eukaryotes, the latter two complexes lack key subunits, encouraging questions about the conservation of their structural design. Here we demonstrate that, in Saccharomyces cerevisiae, Rpn5 plays dual roles by stabilizing proteasome and CSN structures independently. Proteasome and CSN complexes are easily dissected, with Rpn5 the only subunit in common. Together with Rpn5, we identified a total of six bona fide subunits at roughly stoichiometric ratios in isolated, affinity-purified CSN. Moreover, the copy of Rpn5 associated with the CSN is required for enzymatic hydrolysis of Rub1/Nedd8 conjugated to cullins. We propose that multitasking by a single subunit, Rpn5 in this case, allows it to function in different complexes simultaneously. These observations demonstrate that functional substitution of subunits by paralogues is feasible, implying that the canonical composition of the three PCI complexes in S. cerevisiae is more robust than hitherto appreciated.